CHILDREN'S LITERATURE IN THE PROCESSES OF ‘ALFALETRAMENTO’ - Zanelato, Italo Ariel; Bistaffa, Vinicius Marcelino; Shimazaki, Elsa Midori (Literatura em Debate, 2025)
In this qualitative bibliographic research based on Historical-Cultural Theory and Historical-Critical Pedagogy, we discuss the use of children's literature in the learning and development process of the child. To do this, we study concepts related to ‘alfaletramento’, proposed by Magda Soares (2020), and establish dialogues for the analysis of literacy and the schooling of children in the early years of elementary education. The research shows that children's literature: has functions and can humanize and 'hominize'; needs to be presented to students as playful and enjoyable; is an artifact that can be used in the ‘alfaletramento’ process; when offered to students who, due to economic conditions, have less access to it, helps to equip them and appropriate the written culture. Thus, we emphasize the need to use it freely and as a pretext.